Influence of dietary supplementation with Lepidium meyenii (Maca) on sperm quality in dogs - Gattuso, Debora Teresa; Polisca, Angela; Interlandi, Claudia Dina; Rizzo, Maria; Tabbì, Marco; Giudice, Elisabetta; Cristarella, Santo; Rifici, Claudia; Quartuccio, Marco; Zappone, Viola (Frontiers in Veterinary Science, 2024)
Maca is a traditional Andean crop used as a nutraceutical for the fertility-enhancing properties that are linked with antioxidant activity. The aim of this study was to evaluate, for the first time, the potential beneficial effects of oral Maca (Lepidium meyenii or Lepidium peruvianum) supplementation in improving reproductive performance in male dogs. Forty-eight male dogs of different breeds were enrolled in the study, fed the same maintenance diet, and exposed to the same environmental conditions. The subjects were divided into four groups of 12 dogs each: Subfertile treatment group, Subfertile control group, Normofertile treatment group, and Normofertile control group. The dogs in the treatment groups received Lepidium meyenii in their diet in a pill capsule formulation [75 mg/kg Maca extract 10:1, thickening agent (hydroxypropyl methylcellulose), ground rice], while the control groups received placebo pills capsule (starch). For each subject included in the study, the spermiogram was analyzed at three time points of the sperm cycle: at day 0 (T0), day 31 (T31), and day 62 (T62). Dietary supplementation with Maca in subfertile subjects resulted in a significant increase in ejaculate volume and total sperm count compared to the control group. This increase was also observed in normofertile subjects in the treatment group. In addition, total and progressive motility as well as sperm morphology were significantly improved in the groups treated with Maca compared to the control groups. The results thus highlight, for the first time, the potential efficacy of supplementation with 75 mg/kg of Maca extract daily in improving semen quality in dogs.